Role of academia to make current practices of software project risk management more effective: An exploratory study - Janjua, U.I. (Institute of Electrical and Electronics Engineers Inc., 2016)
For a decade or so, academic researchers and practitioners working in the field of software engineering have realized that in order to decrease the failure rate of software project development there is a need to make current practices of risk management more effective. The objective of this study is to explore how academia can play a significant role in making the current practices of software project risk management more effective. To achieve the objective fourteen experts in six different countries were selected to participate in this study. Following the qualitative analysis of open ended questionnaire that the authors undertook, five main related categories have been identified that shape up the role of academia in making current practices of risk management more effective. Â© 2015 IEEE.